Tract-wise microstructural analysis informs on current and future disability in early multiple sclerosis - Ravano, Veronica; Piredda, Gian Franco; Krasensky, Jan; Andelova, Michaela; Uher, Tomas; Srpová, Barbora; Havrdova, Eva Kubala; Vodehnalova, Karolina; Horakova, Dana; Nytrova, Petra; Disselhorst, Jonathan A; Hilbert, Tom; et al. (Journal of neurology, 2024)
OBJECTIVES: Microstructural characterization of patients with multiple sclerosis (MS) has been shown to correlate better with disability compared to conventional radiological biomarkers. Quantitative MRI provides effective means to characterize microstructural brain tissue changes both in lesions and normal-appearing brain tissue. However, the impact of the location of microstructural alterations in terms of neuronal pathways has not been thoroughly explored so far. Here, we study the extent and the location of tissue changes probed using quantitative MRI along white matter (WM) tracts extracted from a connectivity atlas. METHODS: We quantified voxel-wise T1 tissue alterations compared to normative values in a cohort of 99 MS patients. For each WM tract, we extracted metrics reflecting tissue alterations both in lesions and normal-appearing WM and correlated these with cross-sectional disability and disability evolution after 2 years. RESULTS: In early MS patients, T1 alterations in normal-appearing WM correlated better with disability evolution compared to cross-sectional disability. Further, the presence of lesions in supratentorial tracts was more strongly associated with cross-sectional disability, while microstructural alterations in infratentorial pathways yielded higher correlations with disability evolution. In progressive patients, all major WM pathways contributed similarly to explaining disability, and correlations with disability evolution were generally poor. CONCLUSIONS: We showed that microstructural changes evaluated in specific WM pathways contribute to explaining future disability in early MS, hence highlighting the potential of tract-wise analyses in monitoring disease progression. Further, the proposed technique allows to estimate WM tract-specific microstructural characteristics in clinically compatible acquisition times, without the need for advanced diffusion imaging.
Keywords: mozek; White Matter; magnetická rezonanční tomografie; Brain; lidé; Multiple Sclerosis; průřezové studie; Cross-Sectional Studies; Humans; Magnetic Resonance Imaging; bílá hmota; roztroušená skleróza